Characterization of Amorphous Materials by Electron Diffraction and Atomistic Modeling. - Cockayne, D; McKenzie, DR; McBride, W; Goringe, C; McCulloch, D (2000)
The technique of energy selected electron diffraction gives information about amorphous structures which can be used to characterize amorphous materials in terms of their structure. The diffraction data can be used to refine models obtained using molecular dynamics, resulting in physically reasonable models consistent with the diffraction data.